CONODONTS MEETS CLADISTICS: RECOVERING RELATIONSHIPS AND ASSESSING THE COMPLETENESS OF THE CONODONT FOSSIL RECORDS - Donoghue P.C.J. (My University, 2001)
A numerical cladistic analysis of the conodont family Palmatolepidae has been undertaken to determine the applicability of the technique to group-wide systematic revision. Results suggest a new hypothesis of relationships that is considerably more parsimonious than trees compatible with existing hypotheses of relationships, or trees that are even loosely constrained stratigraphically. This may occur either because the fossil record is incomplete, because taxon sampling for the cladistic analysis is low, or because the most parsimonious trees approximate the true tree less well than do stratigraphically-constrained trees (or because of a combination of these factors). Although more taxa and more characters would be preferable in choosing between these possibilities, the tree derived solely from morphological data is adopted. Thus, stratigraphic data can be used to test hypotheses of relationships and construct phylogenies; hypotheses of relationships can be used to test the completeness of the conodont fossil record. Existing schemes of classification within the Palmatolepidae are rejected because most groups within them are either polyphyletic or paraphyletic. A new scheme is presented. Character changes suggest correlated, progressive and mosaic evolution within the Palmatolepidae. Parsimony analysis of partitioned datasets indicates that more phylogenetic information can be recovered from S rather than P or M element positions, although data from all three positional groups are preferable to data from just one. Thus, multielement taxonomy is essential to the resolution of conodont interrelationships.